Interradicular Space in the Anterior Mandible on CBCT Scans of an Iranian Population - S Valizadeh; L Hafezi; A Hasanzdeh Azhiri (Islamic Azad University, 2022)
Abstract Background and Aim: This study aimed to assess the bone thickness at the interradicular spaces in the anterior mandible on cone-beam computed tomography (CBCT) scans of patients to find appropriate sites for mini-implant and miniscrew placement. Materials and Methods: This analytical cross-sectional study was conducted on 161 CBCT scans of patients (98 females and 63 males) between 18 to 50 years old presenting to the School of Dentistry of Islamic Azad University in 2020. Cross-sectional images with 1 mm slice thickness were evaluated to measure the bone thickness at the interradicular areas at 3, 6, 9, 12, 15, and 18 mm distance from the mandibular alveolar crest. The measurements made from the distal surface of right canine to the distal surface of left canine teeth were recorded. The CBCT scans had been taken by Rotograph Evo 3D CBCT scanner, and were analyzed by OnDemand3D software. Data were statistically analyzed by t-test. Results: Bone thickness at 11 sites in the anterior mandible was significantly higher in males (P<0.05). By an increase in depth in both males and females, the mean thickness of bone increased (P<0.05). The maximum mean bone thickness in males and females was at 18 mm depth between the central incisors. Conclusion: To find a correct site for mini-implant and miniscrew placement, it should be noted that bone thickness would be greater at deeper areas, and by moving from the premolar site towards the incisors.